The Unconventional Cytoplasmic Sensing Mechanism for Ethanol Chemotaxis in Bacillus subtilis - Tohidifar, Payman (mBio, 2020)
Motile bacteria sense chemical gradients using chemoreceptors, which consist of distinct sensing and signaling domains. The general model is that the sensing domain binds the chemical and the signaling domain induces the tactic response. Here, we investigated the unconventional sensing mechanism for ethanol taxis in Bacillus subtilis. Ethanol and other short-chain alcohols are attractants for B. subtilis. Two chemoreceptors, McpB and HemAT, sense these alcohols. In the case of McpB, the signaling domain directly binds ethanol. We were further able to identify a single amino acid residue, Ala(431), on the cytoplasmic signaling domain of McpB that, when mutated to serine, reduces taxis to alcohols. Molecular dynamics simulations suggest that the conversion of Ala(431) to serine increases coiled-coil packing within the signaling domain, thereby reducing the ability of ethanol to bind between the helices of the signaling domain. In the case of HemAT, the myoglobin-like sensing domain binds ethanol, likely between the helices encapsulating the heme group. Aside from being sensed by an unconventional mechanism, ethanol also differs from many other chemoattractants because it is not metabolized by B. subtilis and is toxic. We propose that B. subtilis uses ethanol and other short-chain alcohols to locate prey, namely, alcohol-producing microorganisms.